Neuropharmacognosy as an Emerging Multidisciplinary Science - Abdelaziz Ghanemi; Besma Boubertakh (International Journal of Advances in Applied Sciences, 2014)
Neuropharmacognosy  represents  the  field  that  combines  neuroscience  and pharmacognosy.  It  allows  us  to  better  understand  and  use  the  data  that pharmacognosy provides and apply them in neurosciences which may lead to new therapeutic approaches.The  existence  of  both  pharmacological  and  toxicological  aspects  of neuropharmacognosy  creates  more  challenges.  However,  the  methodsprovided by the related  fields, such as chemistry and biology, let us expect more  advances  and  hopefully  new  perspective  that  would  overcome  the current challenges